PENGARUH ESCHERICHIA COLI DAN GRANULOSIT TERHADAP KADAR REACTIVE OXYGEN SPECIES SECARA IN VITRO - Sukarjati; Doddy M. Soebady; Aucky Hinting; Sudjarwo (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2010)
In humans, male genital tract infection has been recognized as one of the causes of infertility. Indicators of the occurrence of genital tract infection are the presence of bacteria during semen culture (bacteriospermia) and the finding of leucocyte of more than 1 million/ml semen (leucotytospermia). Escherichia coli (E. coli) is the most common cause of prostatitis and epididymitis. The objective of this study was to determine the effects of E. coli and granulocytes on Reactive Oxygen Species (ROS) level in vitro. This study comprised of two experiments. In the experiment 1, sperm was incubated with E. coli, and the experiment 2, the sperm was incubated with granulocyte. In those experiments, ROS levels were observed. Spermatozoa were obtained from donor with normal spermatozoa according to WHO (1999). Escherichia coli was obtained by culturing the semen of infertile males. Granulocytes were obtained from donors’ blood. Sperm preparation was made by using Percoll gradient column method. Granulocyte isolation used Histopaque 1077 and 1119. ROS level was detected by means of chemiluminescence method with beta counter device. The result of this study showed that in vitro E. coli had the effect on ROS level, both stimulated by peroxidase (p = 0.000) and PMA (p = 0.006). Granulocyte had effect on ROS level. In peroxidase-stimulated ROS level, there was the effect between spermatozoa and granulocyte-incubated sperm (p = 0.000), granulocyte-incubated sperm and granulocyte (p = 0.002), and sperm and granulocyte (p = 0.000). In PMA-stimulated ROS level, there was effect between sperm and granulocyte-incubated sperm (p = 0.000), sperm and granulocyte (p = 0.000), granulocyte-incubated sperm and granulocyte (p = 0.000). In conclusion, under in vitro experiment, sperm incubated with E. coli and sperm incubated with granulocyte had the effect on the level of the ROS.